1951
DOI: 10.6028/jres.046.024
|View full text |Cite
|
Sign up to set email alerts
|

Viscosity and density of molten optical glasses

Abstract: The viscosities a nd densit ies of 22 op t ical glasses, representin g all ty pes produced at t he National Bureau of Standards, were measured by a co unte rbalanced-sphere method. The densities agreed with those obtained by a vo lumeter method, and t he viscosities showed good agreement with t hose obtained with a small r otation viscometer.Expansivities calulated from density res ults in t he tem peTat ure ran ge 1,000° to 1,200° C showed that flints are low, 15 to 22, barium crowns are in termed iate, 22 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

1951
1951
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(19 citation statements)
references
References 6 publications
1
18
0
Order By: Relevance
“…Recent experience [2] in measuring densities has shown that such an assumption is not valid. The comparison of different properties must be based on measurements made over the same temperature range.…”
Section: D/dt)mentioning
confidence: 99%
See 3 more Smart Citations
“…Recent experience [2] in measuring densities has shown that such an assumption is not valid. The comparison of different properties must be based on measurements made over the same temperature range.…”
Section: D/dt)mentioning
confidence: 99%
“…These densities were determined by a counterbalanced-sphere method [2]. E xpansivities were calcul ated from the change of density with temperatur e. The upper part of figure 5 shows a plot of the surface tensions of lithia-silica liquids at 1,300° C as a function of composition.…”
Section: Measur Ement Of Densitymentioning
confidence: 99%
See 2 more Smart Citations
“…Although borate glass forms a three-dimensional network, its viscosity is substantially lower than that of silicate glass. Again, addition of alkali lowers the viscosity of the melt, but the effect is by no means as dramatic as for silicate glass [44,45]. Introduction of alkali or moisture to alkali metal borate glasses causes some of the three-coordinate boron atoms to become four coordinate [46,47].…”
Section: Introductionmentioning
confidence: 99%